Contexts Rather Than Close Readings of Latin American Literature. Issue 1 (19th March 2023) - Pollard, Scott
Abstract : This essay reviews the following works: Borges and the Literary Marketplace: How Editorial Practices Shaped Cosmopolitan Readings . By Nora C. Benedict. New Haven, CT: Yale University Press, 2021. Pp. ix+ 365. 35.00 hardcover. ISBN: 9780300251418. Oriente no es una pieza de museo: Jorge Luis Borges, la clave orientalista y el manuscrito de "Qué es el budismo." By Sonia Betancort. Salamanca: Ediciones Universidad de Salamanca, 2018. Pp. 316. Paperback. ISBN: 9788490129678. Artesana de sí misma: Gabriela Mistral, una intelectual en cuerpo y palabra. By Claudia Cabello Hut. West Lafayette, IN: Purdue University Press, 2018. Pp. vii + 240. 45.00 paperback. ISBN: 9781557538079. Jorge Luis Borges in Context . Edited by Robin Fiddian. Cambridge: Cambridge University Press, 2020. Pp. viii + 285. 116.00 hardcover. ISBN: 9781108470445. A History of Chilean Literature. Edited by Ignacio López-Calvo. Cambridge: Cambridge University Press, 2021. Pp. xii + 654. 115.00 hardcover. ISBN: 9781108487375. Ascent to Glory: How "One Hundred Years of Solitude" Was Written and Became a Global Classic. By Alvaro Santana-Acuña. New York: Columbia University Press, 2020. Pp. 384. 28.00 paperback. ISBN: 9780231184335.